The effect of pensions on longevity: evidence from Union Army veterans - Martin Salm (Institute for the Study of Labor (IZA), 2007)
This study uses changes in pension laws for Union Army veterans as a natural experiment to estimate the causal effect of pensions on longevity, and to examine potential pathways underlying such a relationship. We examine the effects of the pension laws of 1907 and 1912, which granted old-age pensions to Union Army veterans. Life expectancy for veterans, who received such a pension, increased by 0.5 years and 2.7 years, respectively. The effect of veteran pensions on longevity was large across wealth groups and size of city. Pensions reduced mortality for both acute and non-acute causes of death.
urn:nbn:de:101:1-2008041575
Keywords: 330; Gesetzliche Rentenversicherung; Rentenrecht; Sterblichkeit; Schätzung; Soldaten; USA